#MeToo and the Middle Level - Nicole Hesson (Middle Grades Review, 2022)
The viral #MeToo movement of recent years eventually moved from adult celebrities to harassment in K-12 schools. While many may think of sexual activity and/or harassment beginning in high school, the truth is that many middle school students engage in these behaviors as well. Adolescents have a natural curiosity about their bodies and burgeoning sexuality, but adults often ignore this. Schools should provide more comprehensive sex education in an effort to better inform adolescents and prevent nonconsensual sexual behaviors among younger students.
Keywords: Sex education; #metoo movement